Kinetic of Algae Removal by Photocatalytic Process - โรจน์วิรุฬห์, ธรรมศักดิ์; สิริวิทยาปกรณ์, สัญญา; โรจน์วิรุฬห์, อรวรรณ; อ่างทอง, ศิวกร; สุรเนาวรัตน์, กชกร; ชาวสวน, ณัฐพล (Frontiers in Engineering Innovation Research, 2018)
The objectives of this research are to study the removal efficiency and kinetics of Microcystis aeruginosa TISTR 8305 and Oscillatoria obcura TISTR 8245 by photocatalytic process with TiO2 thin films photocatalyst under low intensity UVA-LED light sources of 12 µW/cm2. The results of algae removal by photocatalytic process showed that the highest removal efficiency for M. aeruginosa TISTR 8305 and O. obcura TISTR 8245 was 83.31% and 73.87%, respectively for initial cell density of 102 cells/mL at 180 minutes. Finally, the kinetics of photocatalytic process for algae removal could be explained by the first-order reaction equation. The first-order reaction rate constants in the photocatalytic process were 0.0099 min-1 and 0.0074 min-1 with initial cell density of 102 cells/mL for M. aeruginosa TISTR 8305 and O. obcura TISTR 8245, respectively.